The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.2353/ajpath.2009.080462
|View full text |Cite
|
Sign up to set email alerts
|

Fn14-TRAIL, a Chimeric Intercellular Signal Exchanger, Attenuates Experimental Autoimmune Encephalomyelitis

Abstract: Hallmarks of the pathogenesis of autoimmune encephalomyelitis include perivascular infiltration of inflammatory cells into the central nervous system, multifocal demyelination in the brain and spinal cord, and focal neuronal degeneration. Optimal treatment of this complex disease will ultimately call for agents that target the spectrum of underlying pathogenic processes. In the present study, Fn14-TRAIL is introduced as a unique immunotherapeutic fusion protein that is designed to exchange and redirect interce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 81 publications
2
35
0
Order By: Relevance
“…As a counterproof, it has been shown that GITR-Fc fusion protein inhibits GITR triggering and protects from the inflammatory response after SCI (Nocentini et al, 2008). In the same line, Razmara et al (2009) showed that Fn14-TRAIL, a chimeric intercellular signal exchanger, attenuates experimental autoimmune encephalomyelitis inflammatory hallmarks. In this study, it is shown that neutralization of TRAIL by in vivo treatment with TRAIL-neutralizing antibody results in diminished expression of GITR and its ligand.…”
Section: Discussionmentioning
confidence: 78%
“…As a counterproof, it has been shown that GITR-Fc fusion protein inhibits GITR triggering and protects from the inflammatory response after SCI (Nocentini et al, 2008). In the same line, Razmara et al (2009) showed that Fn14-TRAIL, a chimeric intercellular signal exchanger, attenuates experimental autoimmune encephalomyelitis inflammatory hallmarks. In this study, it is shown that neutralization of TRAIL by in vivo treatment with TRAIL-neutralizing antibody results in diminished expression of GITR and its ligand.…”
Section: Discussionmentioning
confidence: 78%
“…This response could be designed to counteract the detrimental effects to the pathological elevation of kynurenine metabolites. This is supported by the observation of toxic levels of QUIN and 3-HK that are reached in the spinal cord but not the brain in EAE animals with concomitant increased activity and expression of KMO (67,117,118).…”
Section: Kp and Immune Modulation In The Pathomechanism Of Mssupporting
confidence: 53%
“…Similar to QUIN, the plasma, brain, and spinal cord levels of 3-HK are elevated in EAE rats (118). There is evidence that 3-HK is a neurotoxic metabolite and it, therefore, may have an important role in the neurodegeneration of MS (173).…”
Section: -Hydroxykynureninementioning
confidence: 94%
See 2 more Smart Citations